A Facile synthesis of mesoporous α-Fe2O3/TiO2 nanocomposites for hydrogen evolution under visible light. Issue 10 (July 2020) - Mohamed, Reda M.; Kadi, Mohammad W.; Ismail, Adel A.
Abstract: Mesoporous TiO2 nanoparticles were prepared by a sol-gel process employing the surfactant F127 as the template. α- Fe2 O3 nanoparticles were impregnated onto mesoporous TiO2 surface at different contents (0.1–9 wt%) pursued by annealing at 400 °C. The TEM image of mesoporous Fe2 O3 /TiO2 nanocomposites exhibits the close contact of lattice fringes 0.35 nm of anatase (101) and the lattice spacing of 0.25 nm of the Fe2 O3 (110). The synthesized α-Fe2 O3 /TiO2 nanocomposites were evaluated in the presence of glycerol as hole scavenger for H2 evolution under visible light illumination. Interestingly, the H2 evolution over 5%α- Fe2 O3 /TiO2 nanocomposites was amounted to be 11, 500 μmol/g, which is higher 1150 times than that mesoporous TiO2 . The initial rate of H2 evolution over mesoporous TiO2 is 1 μmolg −1 h −1 which enhanced to 1000 μmolg −1 h −1  at 5 wt% Fe2 O3 /TiO2 nanocomposite. The promoted photocatalytic performance was explained by a positive synergistic effect of α- Fe2 O3 /TiO2 nanocomposites with mesoporous structure, high separation of charge carriers and the enlargement of light harvest. The synthesized α-Fe2 O3 /TiO2 nanocomposites had an elegant photocatalytic activity and exhibited outstanding reusability and stability, which displayed a potential application in energy and environmental fields.